Engineering Mechanics : Dynamics - PYTEL ADDREW (NAIROBI CENGAGE LEARNING, 2016)
Gain a solid understanding of Newtonian dynamics and its application to real-world problems with Pytel/Kiusalaas' ENGINEERING MECHANICS: DYNAMICS, 4E. The text focuses on both fundamental principles and important problem-solving techniques.